Netnography and social network analysis : centrality actors reopening Indonesia's tourism industry in a transitional era - Pipit Fitriyah; Ismi Dwi Astuti Nurhaeni (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Covid-19 disease that the World Health Organization (WHO) stated as a pandemic on March 11, 2020 impacts negatively on the tourism industry. It causes the foreign exchange earnings from the tourism sector to decline, and it is the duty of the Ministry of Tourism and Creative Economy to resolve this problem . The implementation of physical distancing as a solution to minimize the spread of the Covid-19 disease has changed society to do more activities online which speeds up the development of digital culture. The researchers examine the structure of relationships between social entities on Twitter regarding the planning of reopening Indonesian tourism. The data collection is conducted from 19 to 23 June 2020, in the transition era. The subject is the official Twitter account of The Ministry of Tourism and Creative Economy, @kamenparekraf. The netnography method was applied to understand social relations in social networks and analyze the structure and patterns of the relations between community members called actors (nodes) and the relations between members called ties. The results showed that the network formed 5 large clusters that were the clusters of @kamenparekraf, @jokowi, @susipudjiastuti, @wishnutama, and @zenicman. The high level of communication intensity on the planning of reopening tourism during the Covid-19 pandemic indicated that the communication network used Twitter as the favorite social media and formed a digital culture in content using #SobatParekraf so that every actor involved indirectly made social relations and became a member of the Twitter social media community.